Consolidation therapy with autologous stem cell transplantation after remission of induction chemotherapy prolongs the survival of patients with peripheral T-cell lymphoma - Fulati, Wulipan; Ma, Jiexian; Wu, Min; Qian, Wensi; Chen, Pingping; Hu, Yingwei; Chen, Mingyue; Xu, Yu; Huang, Zilan; Zhang, Hongdi; Xie, Yanhui; Shen, Lin (Frontiers in Immunology, 2024)
Background: There was little evidence of autologous stem cell transplantation (ASCT) as consolidation therapy after remission of induction for patients with Peripheral T-cell lymphoma (PTCL). In this study, we conducted a comparative analysis of real-world survival outcomes between consolidation therapy and observation in patients with PTCL. Methods: A total of 92 patients with peripheral T-cell lymphoma (PTCL) who were admitted to the Department of Hematology, Huadong Hospital Affiliated with Fudan University from January 2013 to April 2019 were divided into two groups based on whether they were treated with high-dose therapy (HDT) followed by autologous hematopoietic stem cell transplantation (ASCT): ASCT as consolidation therapy (n=30) and observation (n=62). Clinical characteristics, treatment patterns, and survival outcomes were analyzed between the two groups. Univariate and Cox multivariate regression analyses were also performed to detect prognostic factors of survival. Results: With a median follow-up time of 41 months, the median overall survival (OS) of peripheral T-cell lymphoma patients treated with ASCT was not reached; the median progression-free survival (PFS) was 77.0 months, which was much higher than that of patients without ASCT (p<0.003 for OS, p=0.015 for PFS). Subgroup analysis found that patients with high risks benefited more from ASCT. Combination with hemophagocytic lymphohistiocytosis (HLH) (p<0.001), clinical stage more than III (p=0.014), IPI score above 3 (p=0.049), and bone marrow involvement (p=0.010) were the independent prognostic factors significantly associated with worse OS and PFS. Additionally, pegylated liposomal doxorubicin (PLD)–containing chemotherapy regimen could bring a higher overall response rate (ORR) and prolong the survival of patients with PTCL who underwent ASCT. Conclusion: ASCT may improve the long-term survival of patients with PTCL as consolidation therapy after achieving complete or partial remission of induction treatment, particularly for those with high risks. The chemotherapy regimen containing pegylated liposomal doxorubicin may induce deeper remission than traditional doxorubicin in PTCL. It is crucial to identify the specific groups most likely to benefit from upfront ASCT.